Utilization of Livestock Waste for Organic Production: An Environmentally Friendly and Sustainable Solution - Nurhapsa, Nurhapsa; Rahmawati, Rahmawati; Semaun, Rahmawati; Nurhaedah, Nurhaedah; Mukhlis, Mukhlis (Pascasarjana Universitas Mataram, 2024)
Livestock waste is a source of environmental pollution if not managed properly. Its utilization for organic fertilizer production can be an environmentally friendly and sustainable solution. This community service activity began with location identification in Tallumae Village, Sidrap Regency. counseling and training on making organic fertilizer from cow feces. The training participants had high enthusiasm to gain knowledge about the technology of processing cow feces into environmentally friendly organic fertilizer. The results of the extension and training activities showed a very positive response from farmer groups and communities in Tallumae Village. The existence of farmer groups and community members in Tallumae Village who use organic fertilizer is able to provide a stimulus to the surrounding community to make organic fertilizer from livestock waste. There are even community members who have implemented the organic fertilizer on vegetable crops and the results are very satisfying. The utilization of livestock waste into organic fertilizer can reduce the use of chemical fertilizers